Peculiarities Of Naming Regions - Nargiza Urinovna Komilova (Genius Journals, 2023)
The influence of the ethno-ecological zones based on the heights mentioned in the article can be observed in the formation of settlements in the Fergana Valley. It is noted that development began in the upper, third and fourth ethno-ecological regions of the valley by the population engaged in animal husbandry, horticulture, crafts and dry farming.
Keywords: Hills; horticulture; livestock; farming